Study of the flood in Golestan province from a statistical and synoptics point of view (Case study: March 2019) - Akram Hedayati Dezfuli; Zahra Ghassabi (تحقیقات کاربردی علوم جغرافیایی)
Flood is one of the most destructive natural phenomena. Every year it brings extensive losses to the country’s financial and human resources. In our country, major parts of Iran’s provinces are always at risk of flooding. The Gorgan and Atrak catchments have also become more important, as several floods have occurred in Golestan province in recent years, causing many deaths and economic losses. The purpose of this study was to investigate the synoptic and thermodynamic conditions of the March 2019 flood event in Golestan province in order to atmospheric system that lead to such floods. This study includes statistical analysis of provincial stations (Gorgan, Gonbadkavus, Aliabadkatol, Hashemabad, Kalale, Maravetape and Bandaretokman), calculating of the return period of precipitation during the available statistical period of each station, analysis of synoptic maps on the day of the flood event, the analysis of satellite images of the days involved in the flood, and calculation of instability indices of the Gorgans’s station. Statistical results showed that Gorgan and Gonbadkavus stations, with the highest amount of rainfall in March 2019, had a return period with 800 and 400 years respectively. Also the highest amount index of Gorgan with values of K=26°c, PW= 0.27 cm and TT= 48 was obtained with high relative humidity (about 80%). The analysis of the synoptic maps showed the severe sea level pressure and mid- level height drop with a deep trough in the study area, which led to extreme rainfall. Key words: Flood, return period, Synoptic maps, instability indices, Golestan province.